The Fuelwood Trap - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Munslow B., et al 1988 The Fuelwood Trap: a Study of the SADCC Region ISBN 1-85383- 007-0